Estrutura da comunidade endoparasitária do dourado Salminus brasiliensis (Cuvier, 1816) (Characiformes: Characidae) da planície de inundação do alto rio Paraná, Brasil. - Karling, Letícia Cucolo (2011)
We analyzed 56 specimens of Salminus brasiliensis (Cuvier, 1816) from the upper Paraná River floodplain, collected between March 2009 and August 2010. We identified four parasite taxa: Digenea, Nematoda, Acanthocephala and Cestoda. The most abundant group was Digenea, composed of a single species: Cladocystis intestinalis Vaz, 1932, with a prevalence of 67.85% and 623 specimens. The populations of these parasites showed no concentration for dominance (C <0.25). Some characteristics of the host as the standard length and gonadal maturation stage did not influence the level of parasitism. The community of endoparasite examination showed a typical pattern of aggregation of parasite systems, except for Monticellia coryphicephala Monticelli, 1892, which was found by chance. There were interspecific associations between the peer Octospiniferoides incognita Schmidt & Hugghins, 1973 and Contracaecum sp. larva. There were no significant differences between prevalence and abundance of parasites with the length and stage of gonadal maturation of fish. Significant correlations were recorded between the prevalence of parasitism and host sex and condition factor. There was seasonal variation in levels of parasitism, with higher values recorded in summer. The diversity of endoparasites did not differ significantly between the subsystems of the river floodplain.